1995
DOI: 10.1111/j.1399-6576.1995.tb04078.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral premedication one hour before minor gynaecological surgery — does it have any effect?

Abstract: The purpose of the present study was to compare the effects of oral premedication with ketobemidone 5 mg, lorazepam 1 mg, propranolol 40 mg or placebo, given about an hour prior to anaesthesia, in a prospective randomized double-blind fashion. One hundred and twenty ASA I female patients scheduled for elective laparoscopy were randomly prescribed one of the study drugs. Patient evaluation of anxiety, nurse evaluation of premedication, induction and postoperative course were studied. Ninety-three of the 120 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…They were told that propranolol is approved by the manufacturer (and U.S. Food and Drug Administration) primarily for hypertension, not anxiety, but that it has been used frequently for decades by physicians to treat chronic anxiety, 30 -34 as well as situational anxiety associated with sameday surgery. [35][36][37][38][39][40] From a total of 812 consecutive prospective rhinoplasty patients, nine with early symptomatology were identified, all of whom gave informed consent for participation. Each had a normal blood pressure (100 to 130 mmHg systolic) and pulse rate (70 to 85 beats per minute) and absence of a history of asthma or cardiac disease.…”
Section: Studymentioning
confidence: 99%
“…They were told that propranolol is approved by the manufacturer (and U.S. Food and Drug Administration) primarily for hypertension, not anxiety, but that it has been used frequently for decades by physicians to treat chronic anxiety, 30 -34 as well as situational anxiety associated with sameday surgery. [35][36][37][38][39][40] From a total of 812 consecutive prospective rhinoplasty patients, nine with early symptomatology were identified, all of whom gave informed consent for participation. Each had a normal blood pressure (100 to 130 mmHg systolic) and pulse rate (70 to 85 beats per minute) and absence of a history of asthma or cardiac disease.…”
Section: Studymentioning
confidence: 99%
“…Several trials studying off-label use of propranolol would follow, such as its use in the treatment of high trait anxiety ( Becker, 1976 ; Kathol et al, 1980 ; Meibach et al, 1987 ; Wheatley, 1969 ), substance disorder and withdrawal symptoms ( Grosz, 1972 ), schizophrenia ( Yorkston et al, 1974 ), autism ( Ratey et al, 1987 ), and aggression ( Fleminger et al, 2006 ). In addition, propranolol has been shown to mitigate milder distressing states such as exam nerves ( Brewer, 1972 ; Drew et al, 1985 ; Stone et al, 1973 ), stage fright ( Brantigan et al, 1982 ), performance anxiety in musicians ( Clark and Agras, 1991 ), performance anxiety in surgeons ( Elman et al, 1998 ), and fear of undergoing surgery ( Dyck and Chung, 1991 ; Jakobsson et al, 1995 ; Mealy et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that propranolol has an acute effect on fear-potentiated startle responses [ 89 ]. Additionally, studies on propranolol have indicated that it can alleviate less stressful conditions such as exam anxiety [ 90 , 91 , 92 ], stage fright [ 48 ], performance anxiety in musicians [ 93 ], and fear of surgery [ 94 , 95 ].…”
Section: The Medical Use Of Propranololmentioning
confidence: 99%